1997
DOI: 10.1111/j.1365-263x.1997.tb00268.x
|View full text |Cite
|
Sign up to set email alerts
|

Tooth bud extraction and rubbing of herbs by traditional healers in Tanzania: prevalence, and sociological and environmental factors influencing the practices

Abstract: The practice by traditional healers in Tanzania of extracting tooth buds or of rubbing herbs on to the gingivae of young children to cure fevers and diarrhoea has been known for many years. The aim of this study was to determine the prevalence of these practices in different regions of Tanzania and to identify sociological and environmental factors influencing belief in their efficacy. A total of 1052 children were examined for missing primary teeth, or scars or wounds on the gingivae, resulting from tooth bud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
45
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 3 publications
8
45
0
2
Order By: Relevance
“…Surprisingly, no malformed teeth were found in this population which had some of the subjects born during the time of high pick of infant dental mutilation practices in Tanzania. 11 The results of the current study had Angle's Class II malocclusion twice as much of the previous findings reported among the Tanzanian adolescents. 4,10 A considerable number of individuals with Angle's Class III malocclusion were found in the studied students.…”
supporting
confidence: 73%
“…Surprisingly, no malformed teeth were found in this population which had some of the subjects born during the time of high pick of infant dental mutilation practices in Tanzania. 11 The results of the current study had Angle's Class II malocclusion twice as much of the previous findings reported among the Tanzanian adolescents. 4,10 A considerable number of individuals with Angle's Class III malocclusion were found in the studied students.…”
supporting
confidence: 73%
“…In a study of 1050 children and their parents, Kikuilu et al reported that the major symptoms that led parents to turn to a traditional healer were: persistent fever, diarrhea, vomiting, weight loss, failure to suckle, and crying with unknown cause [10]. The deciduous tooth follicles most often removed are lower canines; the removal is always bilateral [6,8,10]. …”
Section: Discussionmentioning
confidence: 99%
“…The his torical origins of the procedure are not clear but appear to be spread over sev eral countries in East Africa including Somalia, Ethiopia, Sudan, and Uganda. 22 A traditional healer is consulted to lance or remove this area of the gums. The age at which the lancing or extrac tion is carried out varies from as early as one month to three years with peak ages from most studies between four months to 18 months.…”
Section: Discussionmentioning
confidence: 99%